Steel waste valorisation Steel Slag Waste Effect on Concrete Shrinkage - García-Manrique-Ocaña, José Manuel; Parrón, María Eugenia; Rubio Cintas, María Dolores; Oliveira, Miguel José; Silva, Elisa M. J.; Pérez-García, Francisca (My University, 2019)
The concept of sustainability is becoming widespread every day in society, enterprises and institutions. Defining something as sustainable means that the relationship that it establishes with the environment does not represent an aggression or a threat to the latter neither when it is being utilized nor when it stops performing the function for which was designed. To make this happen we need a system in which the main priority is recycling. Everything mentioned above is related to what is called the “Circular Economy”. Concrete is one of the most widely used construction materials in the world. However, the production of portland cement, an essential constituent of concrete, leads to the release of significant amounts of CO22. The global production of concrete represents more than 5% of the anthropogenic emissions of carbon dioxide every year, mainly from the production of cement. The replacement of cement by fly ash and other industrial waste, such as steel slags, is a good example of how resource conservation can be improved and contamination can be reduced. On the other hand, future trends are predicted to increase demand for steel worldwide. Mainly due to the expected improvement in the living standards and demands of underdeveloped populations. The steelmaking process produces a by-product called slag ranging from 10 to 15% per tonne of steel, where reuse is still reduced and much of it is deposited in a landfill. This study presents laboratory test results on the total and autogenous shrinkage of medium strength concrete with partial replacement of cement by slags. Two different slags were tested, namely ladle furnaces slags (LFS) and ground granulated blast furnace slags (GGBFS). The results show the concrete shrinkage behavior when 25% of substitution are used. These data are important to predict future behavior and show that for the substitution dosages used there are no significant divergences for the shrinkage.
Keywords: Cemento; Hormigón; Steel Slag; Concrete Shrinkage; Cement replacement; Waste valorisation